Analysis of Ajaib Application Acceptance Using the UTAUT 2 Model - Muhammad Aldi Pratama; Arista Pratama; Anita Wulansari (Komunitas Dosen Indonesia, 2025)
The rapid advancement of digital technology has greatly expanded investment platforms, especially in the stock and mutual fund sectors. The Ajaib application facilitates easy mobile investing while offering tools and educational resources to help users understand financial markets. This study examines the factors influencing the adoption of Ajaib, utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze data from 400 active Ajaib users. The results reveal that Performance Expectancy, hedonic motivation, price value, social influence, and enabling conditions positively affect adoption. However, Trust and Effort Expectancy were found to have no significant impact on adoption decisions. This suggests that users prioritize the app's performance, social influence, and user experience over trust or ease of use. The study was conducted in Indonesia's fintech market, focusing on the behaviors of Indonesian users. While the findings provide valuable insights into adoption in emerging markets, their generalizability may be limited by socio-economic or cultural differences. Future research should examine demographic factors such as income, age, and education to better understand adoption patterns in various contexts.